Historia magistra vitae: history as education for life in early modern Spain - Gloël, Matthias (Revista de Estudios y Experiencias en Educación, 2020)
The aim of this article is to show the importance of history as education and how it sat example for a good way of life to the people and Princes of early modern Spain. In order to do that, first we characterize what early modern history was and compare the differences to modern times. Next we show the conception of history as a master or teacher for life in specific treaties on that subject all over early modern Europe. People and, especially, Kings are supposed to use these examples to embody the good behavers while dismissing the bad. After this we focus particularly on the Spanish historians and their chronicles, dividing this analysis in two parts. First, we show how in the introductions or prologues to the reader or to patrons the chroniclers explain what history is all about. The same arguments of the theoretical treaties appear again when authors introduce them into their works. Second, we focus on how the same authors give special emphasis to the kings and how their works are supposed to contribute to their education, by learning from the examples and deeds of their Royal peers and predecessors. KEYWORDS: Early modern spain; history of education, history of historiography; chronicles; princely education. Doi: 10.21703/rexe.20201941gloel15